CTLA-4 Synergizes With PD1/PD-L1 in the Inhibitory Tumor Microenvironment of Intrahepatic Cholangiocarcinoma - Guo, Xiao-Jun; Lu, Jia-Cheng; Zeng, Hai-Ying; Zhou, Rong; Sun, Qi-Man; Yang, Guo-Huan; Pei, Yan-Zi; Meng, Xian-Long; Shen, Ying-Hao; Zhang, Peng-Fei; Cai, Jia-Bin; Huang, Pei-Xin; et al. (Frontiers in Immunology, 2021)
Intrahepatic cholangiocarcinoma (ICC) is highly invasive and carries high mortality due to limited therapeutic strategies. In other solid tumors, immune checkpoint inhibitors (ICIs) targets cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) and programmed death 1 (PD1), as well as the PD1 ligand PD-L1 has revolutionized treatment and improved outcomes. However, the relationship and clinical significance of CTLA-4 and PD-L1 expression in ICC remains to be addressed. Deciphering CTLA-4 and PD-L1 interactions in ICC enable targeted therapy for this disease. In this study, immunohistochemistry (IHC) was used to detect and quantify CTLA-4, forkhead box protein P3 (FOXP3), and PD-L1 in samples from 290 patients with ICC. Prognostic capabilities of CTLA-4, FOXP3, and PD-L1 expression in ICC were investigated with the Kaplan-Meier method. Independent risk factors related to ICC survival and recurrence were assessed by Cox proportional hazards models. Here, we identified CTLA-4+ lymphocyte density was elevated in ICC tumors compared to peritumoral hepatic tissues (P <0.001), and patients with a high density of CTLA-4+ tumor-infiltrating lymphocytes (TILsCTLA-4 High) showed a reduced overall survival (OS) rate and increased cumulative recurrence rate compared to patients with TILsCTLA-4 Low (P<0.001 and P=0.024, respectively). Similarly, patients with high FOXP3+ TILs (TILsFOXP3 High) had poorer prognoses than patients with low FOXP3+ TILs (P=0.021, P=0.034, respectively), and density of CTLA-4+ TILs was positively correlated with FOXP3+ TILs (Pearson r= 0.31, P<0.001). Further, patients with high PD-L1 expression in tumors (TumorPD-L1 High) and/or TILsCTLA-4 High presented worse OS and a higher recurrence rate than patients with TILsCTLA-4 LowTumorPD-L1 Low. Moreover, multiple tumors, lymph node metastasis, and high TumorPD-L1/TILsCTLA-4 were independent risk factors of cumulative recurrence and OS for patients after ICC tumor resection. Furthermore, among ICC patients, those with hepatolithiasis had higher expression of CTLA-4 and worse OS compared to patients with HBV infection or undefined risk factors (P= 0.018). In conclusion, CTLA-4 is increased in TILs in ICC and has a distinct expression profile from PD1/PD-L1. TumorPD-L1/TILsCTLA-4 is a predictive factor of OS and ICC recurrence, suggesting that combined therapy targeting PD1/PD-L1 and CTLA-4 may be useful in treating patients with ICC.